(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article investigates the theoretical and practical aspects of integrating artificial intelligence (AI) technologies and digital platforms into the education system. The study analyzes digital transformation processes in the education system of the Republic of Uzbekistan, international best practices, and the impact of AI-based adaptive learning systems on educational quality. A mixed-methods research design was employed, incorporating a questionnaire survey (n=450), a quasi-experimental study (n=120), and statistical analysis. The findings demonstrate that AI-based adaptive learning systems improved student achievement by 25.4 points (47.8%), with a statistically significant difference between experimental and control groups (t=10.15, p<0.001, Cohen’s d=1.93). The article proposes a five-layer conceptual model for the effective integration of AI and digital platforms into Uzbekistan’s education system and develops evidence-based practical recommendations for stakeholders